Concentration of isolated DNA face masks made of gelatin for halal authentication - Hikmah, Nazila Nur; Guntarti, Any; Salamah, Nina (Journal of Halal Science and Research, 2024)
The function of using a face mask is to remove dirt and dead skin cells found in the pores of the skin, open clogged pores and clean the remaining cosmetics that cannot remove with ordinary cleansers, repair and tighten the skin, provide nutrition, smooth, soften and maintain skin moisture. People are aware of halal-labeled cosmetics, one of which is face masks because some face masks contain gelatin. Some face masks on the market contain gelatin. Preparation of 5 reference samples with different concentrations. Preparation of face masks, DNA isolation, and checking the isolation results. The test results with the Nanodrop Spectrophotometer showed that the face mask DNA containing pig and cow gelatin extracted in this study ranged from 163.35 ng/µl in sample S6 to 83.550 ng/µl in sample S7. With the largest concentrations of 163.35 ng/µl and 83.550 ng/µl, while the highest purity value at the λ260/λ280 ratio was 1.41.